Informational features of WhatsApp in everyday life in Madrid: An exploratory study. (February 2023) - Martínez-Comeche, Juan-Antonio; Ruthven, Ian
WhatsApp is one of the most used social media tools, but little is known about its use for everyday purposes. In this study, the informational features of WhatsApp in everyday life in Madrid are analysed through 30 semi-structured interviews, resulting in an informational typology of the messages, a description of the informational purposes of WhatsApp use and descriptions of the social use of WhatsApp. We conclude that WhatsApp allows us to deepen our understanding of the informational habits of people in everyday life.